Variación mensual del índice de gonadosomatico de Colossoma macropomum relacionado a factores ambientales en Cañas, Costa Rica (ING) - Boza, Jorge (2000)
The monthly variation of the gonadosomatic index of Colossoma macropomum in ponds was determined. Monthly, from September 1993 to September 1994, gonad samples of ten individuals were weighed and preserved for histology. Other parameters (precipitation, water temperature and oxygen concentration were taken during all the experimental period. The Gonadosomatic Index (GI) increases rapidly from April to May, remains high from June to August, decreases again from September to November and the lowest values were observed from December to March. The ovarian maduration started one month after the first precipitation was registered (April) and the gonadal regression was related with the minimum monthly precipitation (November), with gonadal quiescency during the dry period from November to March. The values of the gonadosomatic index in males showed the same pattern. Other parameters (water temperature and oxygen concentration) were apparently not related to the gonadosomatic index, probably because of the very small variation during all year.